ANALISIS FAKTOR BUDAYA ORGANISASI,KOMPENSASI,DAN KEMPETENSI TERHADAP KOMITMEN ORGANISASIONAL DI PT PEGADAIAN CABANG PONCOL - Rokhmad Budiyono; Fidyah Yuli Ernawati; Ita Monica (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2022)
The right HRM is the key to success in achieving an organizational goal. The existence of HRM in an organization aims to increase the contribution of employees in the organization. One of the successes of HRM is determined in growing employee organizational commitment. How far the organizational commitment of employees to the organization will greatly determine the achievement of organizational goals. This study aims to determine whether there is an influence between organizational culture, compensation, and competence on organizational commitment at PT. Poncol Branch Pawnshop. The population in this study were all employees of PT. Pegadaian Branch Poncol, with a sample of 35 respondents. The variables in this study are organizational culture, compensation, and competence as independent variables and organizational commitment as the dependent variable. The sampling technique was carried out by the saturated sampling method (Census). The data used is primary data obtained from the distribution of questionnaires and the analytical method used is multiple linear regression analysis. The results of the first hypothesis stated "there is a positive and significant influence between organizational culture on organizational commitment at PT. Pegadaian Branch Poncol with a value (t-count 3.724 > t table 1.696)", hypothesis II states "there is a positive and significant effect between compensation and organizational commitment at PT. Pegadaian Branch Poncol with a value (t-count 4,007 > t table 1,696)", hypothesis III states "there is a positive and significant influence between competence and organizational commitment at PT. Poncol Branch Pawnshop with a value (t-count 3.038 > t-table 1.696)”. The results of the f test are known to be positive and significant with a value (fcount of 10.090 > ftable 2.69) and a p-value of 0.000 <0.05. The results of the coefficient of determination (R2) obtained a figure of 43.7% based on (Adjusted R Square), which means that 43.7% of the independent variables can be explained by the dependent variable and the remaining 56.3% is influenced by other factors that are not researched. Organizational culture has a significant positive effect on organizational commitment, with the better the culture applied by the organization, it is expected to have a positive influence on organizational commitment. Compensation has a positive and significant impact on organizational commitment, it is necessary to optimize the incentive system so that it is more adapted to the duties and responsibilities of each employee. This is expected to increase employee productivity. Competence has a positive and significant influence on organizational commitment, by increasing competence through skills, self-understanding and values ​​that exist within employees, it is hoped that employees can contribute more in increasing organizational commitment at PT. Poncol Branch Pawnshop..